Contractionary Devaluation in Developing Countries : An Analytic Overview. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
This paper evaluates the growing literature on whether devaluation has contractionary effects on output in developing countries. It explores the nature of the links between the exchange rate and real output within a unified, fairly general analytical framework which incorporates a number of the developing-country features cited in this literature. The analysis suggests that many of the arguments on both sides of the contractionary devaluation debate require modification and that a number of potential effects have been ignored. It is concluded that the direction of the impact effects of devaluation on real output is ambiguous on analytical grounds. MASTER FILES ROOM C-130 001.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet